Understanding intractable environmental policy conflicts: the case of the village that would not fall quietly into the sea. Issue 3 (22nd October 2013) - Tebboth, Mark
<x xml:space="preserve">Abstract</x> Coastal erosion is an emotive issue with deeply held views that are often resistant to consensual approaches to identify mutually acceptable solutions. Using the village of Happisburgh on the East Anglian coast in England as a case study, this research analyses how the issue of coastal erosion has been framed and whether the presence of different frames acts as a barrier to building consensus between stakeholders. The study uses Frame Theory and Cultural Theory to understand how the UK Government and the Coastal Concern Action Group (CCAG), a local pressure group based in Happisburgh, communicate and perceive the issue of coastal erosion. Additionally, the study explores whether the different ways of understanding coastal erosion resonate within the community itself. A multi‐method approach was used (policy discourse and media frame analysis) to identify the dominant framings of coastal erosion. The resonance of these frames was tested within the community of Happisburgh through a questionnaire with follow‐up focus groups. The study revealed that the Government discourse of coastal erosion shares many of the characteristics associated with Cultural Theory's hierarchical worldview. Conversely, CCAG's discourse can be likened to the egalitarian position. The community of Happisburgh was found to strongly agree with the discourse that is representative of an egalitarian worldview. Furthermore, there was an increased uniformity of views regarding coastal erosion compared with attitudes towards nature more generally. The study concludes that different framings act as a barrier to building consensus. Efforts should be made to develop governance solutions to tackle the explicit disagreements (revealed in this study) whilst acknowledging the more implicit origins of these differences.